Social Assistance At Yaa Bunayya Orphanage, Batam City, Riau Islands Province - Mulyadi, Tirta; Ilham, Wahyudi; Atmaja, Hari Sandi; Yusuf, Abd Rahman (JURNAL KEKER WISATA, 2025)
Abstract This study explores the implementation of social assistance programs at Yaa Bunayya Orphanage in Batam City, Riau Islands Province. The orphanage serves as a haven for underprivileged and orphaned children, offering both care and education. Social assistance from the government and community is integral to ensuring the smooth operation of the orphanage and supporting the well-being of its residents. Using a qualitative approach with a case study method, data were collected through interviews with orphanage staff, donors, and the children. The findings highlight that the assistance provided includes financial aid, food, clothing, and educational support. The study also uncovers challenges in the distribution process and suggests strategies to improve the efficiency and impact of future assistance. These insights aim to emphasize the importance of collective efforts in enhancing the welfare of orphaned children and the sustainability of orphanage operations in Batam.